Comparative features and outcomes of major neurological complications of COVID-19 - Beghi E; Moro E; Davidescu EI; Popescu BO; Grosu O; Valzania F; Cotelli MS; Kiteva Trenchevska G; Zakharova M; Kovács T; Armon C; Brola W; et al. (Wiley-Blackwell, 2022)
Background and purpose: The aim of this study was to assess the neurological complications of SARS- CoV- 2 infection and compare phenotypes and outcomes in infected patients with and without selected neurological manifestations. Methods: The data source was a registry established by the European Academy of Neurology during the first wave of the COVID- 19 pandemic. Neurologists collected data on patients with COVID- 19 seen as in- and outpatients and in emergency rooms in 23 European and seven non- European countries. Prospective and retrospective data included patient demographics, lifestyle habits, comorbidities, main COVID- 19 complications, hospital and intensive care unit admissions, diagnostic tests, and outcome. Acute/ subacute selected neurological manifestations in patients with COVID- 19 were analysed, comparing individuals with and without each condition for several risk factors. Results: By July 31, 2021, 1523 patients (758 men, 756 women, and nine intersex/unknown, aged 16– 101 years) were registered. Neurological manifestations were diagnosed in 1213 infected patients (79.6%). At study entry, 978 patients (64.2%) had one or more chronic general or neurological comorbidities. Predominant acute/subacute neurological manifestations were cognitive dysfunction (N = 449, 29.5%), stroke (N = 392, 25.7%), sleep– wake disturbances (N = 250, 16.4%), dysautonomia (N = 224, 14.7%), peripheral neuropathy (N = 145, 9.5%), movement disorders (N = 142, 9.3%), ataxia (N = 134, 8.8%), and seizures (N = 126, 8.3%). These manifestations tended to differ with regard to age, general and neurological comorbidities, infection severity and non- neurological manifestations, extent of association with other acute/subacute neurological manifestations, and outcome. Conclusions: Patients with COVID- 19 and neurological manifestations present with distinct phenotypes. Differences in age, general and neurological comorbidities, and infection severity characterize the various neurological manifestations of COVID-19.
Keywords: COVID-19; coronavirus; neurological complications; neurology